2011
DOI: 10.1111/j.1528-1167.2011.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric outcomes of epilepsy surgery: A systematic review

Abstract: SUMMARYPurpose: The objective of this systematic review was to identify: (1) prevalence and severity of psychiatric conditions before and after resective epilepsy surgery, (2) incidence of postsurgical psychiatric conditions, and (3) predictors of psychiatric status after surgery. Methods: A literature search was conducted using PubMed, EmBase, and the Cochrane database as part of a larger project on the development of an appropriateness and necessity rating tool to identify patients of all ages with potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 23 publications
2
59
2
2
Order By: Relevance
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 56%
“…1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs. The follow-up period and patient selection criteria might partly explain these discrepancies, as our subgroup of patients with postoperative psychiatric disorders was limited to patients who received psychotropic drugs 2 or more years after the surgery.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Psykiatrisk komorbiditet, inkludert angst, depresjon, atferdsforstyrrelser og psykoser, ble tidligere ansett som en relativ kontraindikasjon til kirurgi. I de senere år har man imidlertid endret holdning, idet man har sett at psykiatriske symptomer som regel ikke blir verre etter inngrepene, i mange tilfeller tvert imot (14,15). Pasienter med betydelig psykiatrisk komorbiditet har allikevel mindre sjanse for å bli anfallsfrie etter resektiv kirurgi enn pasienter uten slike problemer (14,15).…”
Section: Psykiatrisk Utredningunclassified